Manual of standardization in the Romance languages - Lebsanft, Franz; Tacke, Felix (Manuals of Romance linguistics, 2020)
Frontmatter -- Manuals of Romance Linguistics -- Preface -- Table of Contents -- Abbreviations -- Introduction -- 0. Romance Standardology: Roots and Traditions / Lebsanft, Franz / Tacke, Felix -- Theories of Linguistic Norm -- 1. Linguistic Norm in Classical Grammar and Rhetoric / Fesenmeier, Ludwig -- 2. Linguistic Norm in the Prague School of Linguistics / Albrecht, Jörn -- 3. Linguistic Norm in the Linguistic Theory of Eugenio Coseriu / Kabatek, Johannes -- 4. Linguistic Norm in Sociolinguistics / Sinner, Carsten -- 5. Linguistic Norm in Linguistic Pragmatics / Schrott, Angela -- 6. Linguistic Norm in Cognitive Linguistics / Tacke, Felix -- 7. Linguistic Norm in Discourse Linguistics / Lebsanft, Franz -- Instruments and Reference Tools for Language Codification and Modernization -- 8. Romanian -- 8.1 Orthography and Orthoepy / Stan, Camelia -- 8.2 Normative Grammars / Zafiu, Rodica -- 8.3 Normative Dictionaries / Zafiu, Rodica -- 8.4 Dictionaries of Language Difficulties / Nedelcu, Isabela -- 9. Italian -- 9.1 Orthography and Orthoepy / Bernhard, Gerald -- 9.2 Normative Grammars / Roberto, Elisa De -- 9.3 Normative Dictionaries / Lorenzetti, Luca -- 9.4 Dictionaries of Language Difficulties / Lorenzetti, Luca -- 10. French -- 10.1 Orthography and Orthoepy / Pöll, Bernhard -- 10.2 Normative Grammars / Große, Sybille -- 10.3 Normative Dictionaries / Melchior, Luca -- 10.4 Dictionaries of Language Difficulties / Wolf, Johanna -- 11. Catalan -- 11.1 Orthography and Orthoepy / Paloma, David -- 11.2 Normative Grammars / Brumme, Jenny -- 11.3 Normative Dictionaries / Bernal, Elisenda -- 11.4 Dictionaries of Language Difficulties / Martí, Òscar Bladas -- 12. Spanish -- 12.1 Orthography and Orthoepy / Tacke, Felix -- 12.2 Normative Grammars / Amorós-Negre, Carla -- 12.3 Normative Dictionaries / Greußlich, Sebastian -- 12.4 Dictionaries of Language Difficulties / Lebsanft, Franz -- 13. Portuguese -- 13.1 Orthography and Orthoepy / Filomena Gonçalves, Maria -- 13.2 Normative Grammars / Silva, Augusto Soares da -- 13.3 Normative Dictionaries / Mühlschlegel, Ulrike -- 13.4 Dictionaries of Language Difficulties / Gonçalves, Maria Filomena -- 14. “Minor” Romance Languages -- 14.1 “Minor” Italo-Romance Languages / Heinemann, Sabine -- 14.2 “Minor” Gallo-Romance Languages / Reutner, Ursula -- 14.3 “Minor” Ibero-Romance Languages / Postlep, Sebastian -- 14.4 Romance-based Creoles / Patzelt, Carolin -- Index of subjects